Factors Associated With Recurrence Of Epithelial Ovarian Cancer In RSUP Dr. Kariadi Semarang - Kurube, Isabela Marsialina; Ambari, Ediwibowo; Iskandar, Teuku Mirza; Tjahjanto, Hary; Dewantiningrum, Julian; Mochtar, Arufiadi Anityo; Trisetiyono, Yuli (Faculty of Medicine, Diponegoro University, 2022)
Introductions: Epithelial ovarian cancer accounts for 90% of all ovarian malignancies. More than 70% of patients will experience a relapse even after receiving operative therapy and chemotherapy. There are several prognostic factors that influence the recurrence of ovarian cancer. In Indonesia, especially at Dr. Kariadi Hospital, Semarang, the data as mentioned above is still very limited.objective: Knowing the disease-free survival rate, optimizing surgery and factors related to the incidence of recurrence in epithelial ovarian cancer patients at Dr. Kariadi Hospital SemarangMethods: This study is a retrospective cohort study with survival analysis. Data were collected through medical records, with the study population are patients with a diagnosis of epithelial ovarian cancer who were treated at Dr. Kariadi Hospital Semarang in period January 2018-December 2019. Furthermore, patients who had been remission were observed for signs of disease recurrence for 2 years period.Results: There were 361 patients with epithelial ovarian cancer who underwent primary treatment at Dr. Kariadi Hospital, Semarang in 2018-2019. Furthermore, there were observations of recurrence in 148 patients who achieved remission. Of these 76 patients (51.4%) experienced recurrence, while 72 patients not relapse. From 148 epithelial ovarian cancer patients who underwent cytoreduction surgery at Dr. Kariadi Hospital, Semarang, 113 patients (76.4%) achieved optimal operation with a residu less than 2 cm, while 35 patients (23.6%) were not optimal with a residu more than 2 cm. FIGO stage (HR 2.44) and tumor residu (HR 2.15) were shown to be significant factors associated with the recurrence of epithelial ovarian cancer.Conclusion: Overall disease-free survival in epithelial ovarian cancer at Dr. Kariadi Semarang were 74.8% (6 months), 57.1% (1 year), 42.5% (18 months), and 37.4% (2 years). Tumor residual factors and FIGO stage were shown to be significant prognostic factors influencing the recurrence of epithelial ovarian cancer.